The correct equation is:
6x² + 19x+ 4 = 2x -1
The general form of the quadratic equation is:
ax² + bx + c = 0
We need to put our equation in general form:
6x² + 19x+ 4 = 2x -1
6x² + 19x+ 4 - 2x +1 = 0
6x² + 17x + 5 = 0
By comparing our equation with the general form, we would find that:
a = 6
b = 17
c = 5
Now, to get the solution, we will substitute with the values of a, b and c in the quadratic formula shown in the attached image
This will give us the following solutions:
either x = [tex] \frac{-17+ \sqrt{(17)^2-4(6)(5)} }{2(6)} = \frac{-1}{3} [/tex]
or x = [tex] \frac{-17- \sqrt{(17)^2-4(6)(5)} }{2(6)} = \frac{-5}{2} [/tex]
Hope this helps :)